Respuesta :
Answer:
f[g(6)] = 0
Step-by-step explanation:
∵ f(x) = 6x + 12
∵ g(x) = x - 8
∴ f(g(6)) = f(6 - 8) = f (-2)
∴ f(-2) = 6(-2) + 12 = -12 + 12 = 0
∴ f[g(6)] = 0
Answer:
f(g(6)) = 0
Step-by-step explanation:
We have given two functions.
f(x) = 6x + 12 and g(x) = x − 8
We have to find the value of f[g(x)] at x = 6.
Putting values , we have
f(g(x) = f(x-8)
f(g(x) = 6(x-8)+12
f(g(x) = 6x-48+12
f(g(x) = 6x-36
Putting x = 6 in above equation ,we have
f(g(6) = 6(6)-36
f(g(6)) = 36-36
f(g(6)) = 0 which is the answer.